Improving the Ability to Write Observation Report Texts through Canva Media and Project-Based Learning Methods for Class VII Students of SMP Negeri 1 Sungai Menang - Natalia, Ayu; Wardarita, Ratu; Rukiyah, Siti (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study aims to determine and describe the application of Canva to improve the ability to write observation report texts (LHO) through the project learning model for class VII students of SMP Negeri 1 Sungai Menang. This study includes Classroom Action Research (CAR) with 36 students as research subjects. The data collection method uses test, observation, and documentation methods. The data analysis technique uses quantitative methods to observe teacher performance and assess student work in the form of LHO texts. The results of the study showed that the use of Canva media and the project learning model improved the quality of learning to write LHO texts. Teacher activity in cycle I with a total score percentage obtained of 84% increased to 88% in cycle II. The total value of students' LHO text writing skills in cycle I obtained 2293 or the average classical student score was 63.70 with a percentage of completion of 36%. In cycle II, the total value of LHO text writing skills increased by 3099 or the average classical score was 86.10 with a percentage of completion reaching 100%.